2021
DOI: 10.1007/s10879-021-09503-w
|View full text |Cite
|
Sign up to set email alerts
|

Telepsychotherapy During the COVID-19 Pandemic: The Experience of Lebanese Mental Health Professionals

Abstract: The COVID-19 pandemic has taken the mental health system by surprise, with the state of lockdown forcing businesses to close their doors, including many mental health services. This has driven many psychotherapists and other mental health professionals towards telepsychotherapy, relying on online consultations to provide continuity of care. However, the adoption of telepsychotherapy required major adaptations from both mental health professionals and patients. This study set out to explore the predictors of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Despite preferring face-to-face sessions, research shows that the more experience one has with online consultations, the more confident they feel about conquering the obstacles of telepsychotherapy. [ 43 ] Studies have demonstrated that cognitive-behavioural phone-based treatments are useful for patients suffering from anxiety, sadness, or obsessive-compulsive disorder. [ 44 45 ]…”
Section: Discussionmentioning
confidence: 99%
“…Despite preferring face-to-face sessions, research shows that the more experience one has with online consultations, the more confident they feel about conquering the obstacles of telepsychotherapy. [ 43 ] Studies have demonstrated that cognitive-behavioural phone-based treatments are useful for patients suffering from anxiety, sadness, or obsessive-compulsive disorder. [ 44 45 ]…”
Section: Discussionmentioning
confidence: 99%
“…They focused on the validation of different stress and anxiety scales in order to measure the level of psychological distress among the general population and correlate them with different socio-demographic factors aggravating their mental distress [41][42][43][44][45][46][47][48][49]. More research has examined the role of media coverage of diseases in in uencing people's health behavior, particularly their compliance with prevention measures through online consultations [50,51]. It was proven that increased media exposure to COVID-19 news positively relates to people's abidance by prevention measures and that perceived knowledge and fear mediate this relationship [52].…”
Section: Study Objectives and Endpointsmentioning
confidence: 99%
“…Unprecedented changes to traditional psychotherapeutic practice arose from the lockdown restrictions associated with the COVID‐19 pandemic. These changes to practice included the imposed change to the therapeutic frame: transitioning clients from face‐to‐face meetings to delivery of psychotherapy sessions via videoconferencing, defined here as telepsychotherapy (Poletti et al, 2021; Tohme et al, 2021). Online therapy was an already growing industry prior to the COVID‐19 pandemic and is likely to continue to expand in utilisation postlockdown restrictions (Lin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Given the recent nature of events that occurred from the pandemic lockdowns, impacting practice by imposing a change from face‐to‐face meetings to online sessions, research and insight into the potential impact on the clinician, the client and the therapeutic process is still yet to be thoroughly understood. There are a number of studies that have documented some important and emerging findings (e.g., Aafjes‐van Doorn et al, 2020; Békés et al, 2020; Humer et al, 2020; Shklarski et al, 2021; Tohme et al, 2021). These studies have been primarily survey‐based in design and have investigated various aspects of telepsychotherapy with findings relating to the following: technology disruptions and challenges inherent in the use of telepsychotherapy; the therapeutic relationship after the transition (Békés et al, 2020); aspects relating to the therapeutic relationship (professional self‐doubt and anxiety; Aafjes‐van Doorn et al, 2020); predictors related to the uptake of telepsychotherapy by mental health professionals (e.g., previous experience with online therapy; Tohme et al, 2021); decisions affecting the return to in‐person therapy (Shklarski et al, 2021); and the impact of therapeutic orientation on attitudes towards telepsychotherapy (Humer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation